2011
DOI: 10.1249/mss.0b013e31820751cb
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Does Not Augment Exercise-Induced Protein Accretion versus Protein Alone

Abstract: Our data suggest that insulin is not additive or synergistic to rates of MPS or MPB when CHO is coingested with a dose of protein that maximally stimulates rates of MPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 29 publications
8
124
1
5
Order By: Relevance
“…In line with our observations, the co-ingestion of carbohydrates with casein protein lowered plasma AA levels in older adults [39], and also delayed digestion and absorption kinetics using intrinsically labelled casein [26]. Only one study in young adults showed lower peak plasma levels of leucine, branched chain amino acids (BCAA) and EAA when whey protein was co-ingested with carbohydrates [40]. Two studies, in young adults with intrinsically labelled milk protein, showed that the addition of carbohydrates and fat delays gastric emptying of milk protein and slows the release of dietary nitrogen to the periphery [27,41].…”
Section: Effect Of Caloric Densitysupporting
confidence: 87%
“…In line with our observations, the co-ingestion of carbohydrates with casein protein lowered plasma AA levels in older adults [39], and also delayed digestion and absorption kinetics using intrinsically labelled casein [26]. Only one study in young adults showed lower peak plasma levels of leucine, branched chain amino acids (BCAA) and EAA when whey protein was co-ingested with carbohydrates [40]. Two studies, in young adults with intrinsically labelled milk protein, showed that the addition of carbohydrates and fat delays gastric emptying of milk protein and slows the release of dietary nitrogen to the periphery [27,41].…”
Section: Effect Of Caloric Densitysupporting
confidence: 87%
“…For instance, differences in nutrition [15,16,40], sleep [41], habitual physical activity [42,43] and genetic variations/polymorphisms [44][45][46] can modulate MPS and hypertrophic responses. Thus, it is plausible to assume that it would be the integrated response of summed RE bouts, nutrition, sleep, general activity and genetic predisposition of free-living humans that would yield a phenotypic outcome of RT.…”
Section: Acute Temporal Changes In Muscle Protein Synthesis In Differmentioning
confidence: 99%
“…For example, the food matrix can affect digestion and absorption with liquid protein sources eliciting a more rapid increase and a greater peak amino acid concentration than solid foods of equivalent protein content (63). However, the inclusion of additional energy in the form of carbohydrates does not appear to affect the utilization of dietary amino acids from high-quality protein sources (e.g., whey/casein) for the synthesis of muscle proteins in young or older adults (64)(65)(66). Nevertheless, whole-food protein sources that are more easily masticated and digested (e.g., minced beef compared with beef steak) result in a more rapid dietary amino acid appearance in the blood and a greater net whole-body protein retention in older adults (67,68).…”
Section: Metabolic Regulation Of Skeletal Muscle Massmentioning
confidence: 99%